Rehabilitation Legislation of Disabled Persons in the View of Health Rights - Juan ZHANG (康复学报)
Now the rehabilitation legislation of the disabled persons is not systematic and specific in China. The rights of the disabled persons as the special-subject of health rights are not prominent, which leads to the rehabilitative interests of the disabled persons can't be protected effectively. In consideration of the relationship between medicine and law, the article points out that the concept of the health right in the civil law should be extend firstly; the health rights which have the dual nature with civil rights and basic rights should be recognized secondly; because of the attributes of their basic rights, the health rights should be written in the constitution thirdly; at last, based on the modern concept of rehabilitation, the disabled persons who want to realize their health rights need to pay attention to the legislation of social law, especially the community rehabilitation, and the establishment and improvement of social insurance'system. In the view of health rights, the article reviews the rehabilitation legislation of the disabled persons in the existing legal system, and seeks to provide some theories and policy resources for the improvement of our rehabilitation legislation of the disabled persons by comparing and learning from foreign advanced legislation.